Ralstonia solanacearum – A soil borne hidden enemy of plants: Research development in management strategies, their action mechanism and challenges - Wang, Zhaojun; Luo, Wenbo; Cheng, Shujia; Zhang, Hongjie; Zong, Jing; Zhang, Zhe (Frontiers in Plant Science, 2023)
Plant pathogens present in soil cause severe losses to plants every year. Among them, Ralstonia solanacearum, because of its destructive nature, is the world's second most damaging bacterial phytopathogen. Over 310 species of plants belonging to 42 plant families are infected by this deadly pathogen. Around the world, the BW disease causes yield losses that range from 20 to 100%. Control measures for managing this pathogen comprises several diverse approaches. Regardless of whether several control methods are developed to manage the BW disease, efficient management strategies with eco-friendly effects and the desired level of effective control is still awaited and there is need to developed effective management methods to eliminate this fetal disease in several crops under field conditions. An analysis of development in the management strategies will provide an effective way to search and develop control methods with desirable level of effectiveness. In this review, we discussed and analyzed the information reported on the development of various management strategies for the management of R. solanacearumalong with the comprehensive presentation on action mechanism of these management strategies. We have also made an effort to summarize the challenges that make hurdle in the effective management of this deadly pathogen.